Dietary N-nitroso compounds and risk of colorectal cancer: a case–control study in Newfoundland and Labrador and Ontario, Canada. Issue 6 (25th October 2013) - Zhu, Yun; Wang, Peizhon Peter; Zhao, Jing; Green, Roger; Sun, Zhuoyu; Roebothan, Barbara; Squires, Josh; Buehler, Sharon; Dicks, Elizabeth; Zhao, Jinhui; Cotterchio, Michelle; Campbell, Peter T.; et al.
Abstract : Several N -nitroso compounds (NOC) have been shown to be carcinogenic in a variety of laboratory animals, but evidence of their carcinogenicity in humans is lacking. We aimed to examine the association between NOC intake and colorectal cancer (CRC) risk and possible effect modification by vitamins C and E and protein in a large case–control study carried out in Newfoundland and Labrador and Ontario, Canada. A total of 1760 case patients with pathologically confirmed adenocarcinoma and 2481 population controls were asked to complete a self-administered FFQ to evaluate their dietary intakes 1 year before diagnosis (for cases) or interview (for controls). Adjusted OR and 95 % CI were calculated across the quintiles of NOC (measured by N -nitrosodimethylamine (NDMA)) intake and relevant food items using unconditional logistic regression. NDMA intake was found to be associated with a higher risk of CRC (highest v. lowest quintiles: OR 1·42, 95 % CI 1·03, 1·96; P for trend = 0·005), specifically for rectal carcinoma (OR 1·61, 95 % CI 1·11, 2·35; P for trend = 0·01). CRC risk also increased with the consumption of NDMA-containing meats when the highest tertile was compared with the lowest tertile (OR 1·47, 95 % CI 1·03, 2·10; P for trend = 0·20). There was evidence of effect modification between dietary vitamin E and NDMA. Individuals with high NDMA and low vitamin E intakes had a significantly increased risk than those with both low NDMA and low vitamin E intakes (OR 3·01, 95 % CI 1·43, 6·51; P for interaction = 0·017). The present results support the hypothesis that NOC intake may be positively associated with CRC risk in humans. Vitamin E, which inhibits nitrosation, could modify the effect of NDMA on CRC risk.